Linking Complement C3 and B Cells in Nasal Polyposis - Ulrike Werner; Axel Künstner; Maren Drenckhan; Ralph Pries; Karl-Ludwig Bruchhage; Hauke S. Busch; Claus Bachert; Barbara Wollenberg (Journal of Immunology Research)
Nasal polyposis often is characterized by a persistent inflammation of the sinonasal mucosa, disease recurrence after medical or surgical intervention, and asthma comorbidity. Dysregulated complement activation may contribute to immunologic alterations and disease. To date, there is only scattered knowledge on the source and regulation of the central complement factors in the pathogenesis of nasal polyps. Here, we aim to study complement signatures, especially the C3-C3aR axis, and focus on cellular sources and targets in nasal polyps. Expression of complement factors, including C3, C5, and the anaphylatoxin receptors, was analyzed in nasal polyp tissue samples, the corresponding inferior turbinates, and healthy controls using transcriptomic methods and protein measurements. Distinct patterns of complement expression were found in nasal polyps compared to controls, characterized by an increased C3 activation and an increase in C3aR-bearing cells. In contrast, no difference was shown for epithelial-dependent C3 production. Besides low intracellular C3-expression levels for lymphocytes in general, we could identify an enlarged B lymphocyte population in nasal polyps displaying high amounts of intracellular C3. Our data suggest a prominent role for the C3-C3aR-axis in nasal polyps and, for the first time, describe a B cell population containing high levels of intracellular C3, suggesting a new role of B cells in the maintenance of the inflammation by complement.